Tolerance, fermentation, and cytokine expression in healthy aged male C57BL/6J mice fed resistant starch - Zhou, June; Keenan, Michael J.; Keller, Jeffrey; Fernandez-Kim, Sun O.; Pistell, Paul J.; Tulley, Richard T.; Raggio, Anne M.; Shen, Li; Zhang, Hanjie; Martin, Roy J.; Blackman, Marc R. (Molecular nutrition & food research, 2012)
Health benefits of resistant starch (RS), a dietary fermentable fiber, have been well documented in young, but not in old populations. As the essential step of more comprehensive evaluations of RS on healthy aging, we examined the effects of dietary RS on tolerance, colonic fermentation, and cytokine expression in aged mice. Healthy older (18‐20 months) C57BL/6J male mice were fed control, 18% RS, or 36% RS diets for 10 weeks. Body weight gain, body composition, and fat pad weights did not differ among the three groups after 10 weeks, indicating good tolerance of the RS diet. Fermentation indicators (cecum weights, and cecal proglucagon and PYY mRNA expression) were enhanced in an RS dose‐dependent manner (p<0.01). Serum concentrations of soluble cytokine receptors (sTNF‐Rb, sIL‐4R, sIL‐2Rα, sVEGFR1, and sRAGE) and TNFα expression (gene and protein) in visceral fat did not differ significantly among groups. Adiponectin protein concentrations, but not gene expression, were greater in epididymal fat of the 36% RS versus control groups (p<0.05). As a conclusion in aged mice, dietary RS is well tolerated, fermented in the colon, and stimulates colonic expression of proglucagon and PYY mRNA, and adiponectin protein in visceral fat.